CFD Simulation of Particle Residence Time in Small and Industrial Scale Spray Dryer - Noor Intan Shafinas, Muhammad; Jolius, Gimbun (2014)
This paper presents a CFD study of short and tall spray dryers. The simulations were performed using turbulent model; standard k-ε (SKE), realizable k-ε (RKE) and the Detached Eddy Simulation (DES). The predicted axial velocity, temperature and humidity profile inside the spray drying chamber were found to be in fair agreement to the experimental data adapted from literature for model tested in this work. The Detached Eddy Simulation provides more accurate prediction of fluid flow in a co-current spray dryer. Moreover, particle tracking has been included using the source-in-cell method to enable calculation of particle residence time (RTD) and their impact positions in the drying chamber. This study suggests that the tall spray dryer has less overall residence time than the shorter one due to lesser recirculation.